Lightweight flexible carbon nanotube/polyaniline films with outstanding EMI shielding properties. Issue 34 (21st August 2017) - Li, Hui; Lu, Xuehong; Yuan, Du; Sun, Jiaotong; Erden, Fuat; Wang, Fuke; He, Chaobin
Abstract : Flexible and highly conductive CNT/PANI films were developed for EMI shielding applications, which exhibited the highest specific shielding effectiveness among those reported. Abstract : Lightweight flexible carbon nanotube (CNT)/polyaniline (PANI) free standing films having the highest reported specific shielding effectiveness (SSE) of 7.5 × 10 4 dB cm 2 g −1 were developed using amine-functionalized CNTs, which could be attributed to the high conductivity (3009 S cm −1 ) and low density of the amine-functionalized CNT/PANI composites. The mechanism behind the high conductivity is also studied.